EVALUATION OF THE USE OF THE STATE CIVIL APPARATUS MANAGEMENT INFORMATION SYSTEM (SIMASGARA) AT THE MANDAILING NATAL PERSONNEL AGENCY - Tamrin, Husni; Ritonga, Syafruddin; Musthafa, Walid (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
This study aims to evaluate the use of the State Civil Apparatus Management Information System (SIMASGARA) at the Mandailing Natal Regency Civil Service Agency. SIMASGARA is a digital system designed to manage data and personnel administration effectively. This study uses a qualitative approach with an exploratory descriptive design, which involves in-depth interviews, direct observation, and document analysis to obtain comprehensive data. The subjects of the study include operational employees, leaders of the Personnel Agency, and other system users related to ASN data management. The results of the study show that SIMASGARA has provided significant benefits in personnel data management, especially in simplifying administrative processes, improving data accuracy, and accelerating the preparation of reports. However, the use of this system is still not optimal. The main obstacles found include limited network infrastructure, lack of user understanding of system features, and resistance to changing from manual to digital methods. Leadership support and policies that require the use of SIMASGARA are the main supporting factors for the successful implementation of this system. This study also identifies that the success of SIMASGARA is influenced by organizational readiness, technical infrastructure, and individual competence, as explained in the theory of Technology Acceptance Model (TAM) and Diffusion of Innovation. To overcome existing obstacles, the recommendations include advanced training to improve user competence, strengthening technology infrastructure, and developing a digital-based work culture. This study concludes that SIMASGARA has great potential to support bureaucratic reform, especially in personnel management. However, system optimization requires a holistic and sustainable strategy. With the right improvements, SIMASGARA can become a model for the implementation of an effective personnel information system in the public sector.